Resilience-based seismic design based on time-to-functionality for tall mass timber buildings - Furley, Jace, author; van de Lindt, John, advisor; Arneson, Erin, committee member; Guo, Yanlin, committee member; Mahmoud, Hussam, committee member (Colorado State University. Libraries, 2023)
Mass timber has existed for years as a structural material; however, only in the last decade or so has progress been made in North America on the adoption of mass timber for moderate to high seismic regions. During this time, there has been significant research effort and resources allocated to demonstrating various mass timber products as suitable for seismic applications, in particular as seismic force resisting systems (SFRS). However, during the research process, the potential suitability of mass timber for mid-rise or tall buildings was identified, and research efforts into the applicability of mass timber for taller buildings in seismic regions have been increasing in the past several years. Along with the growing interest in mass timber for tall buildings, a larger more general push for resilient buildings and communities has also been prevalent, providing the opportunity to design mass timber SFRS for tall buildings that not only meet current performance standards, but also have the potential to contribute to resilience-based design and ultimately community resilience. This research presented in this dissertation develops and applies the time-to-functionality fragility (TTF) methodology to provide resilience-based design guidance for tall mass timber buildings. The new TTF methodology incorporates many of the considerations of previous performance-based methodologies (such as FEMA P-58) and resilience methods (such as the REDi rating system) into a multi-layer direct Monte Carlo simulation to estimate various recovery levels. This method was then applied to a two-story test specimen utilizing a new mass timber SFRS (a cross laminated timber [CLT] rocking wall), developed as a part of the Natural Hazards Equipment Research Infrastructure (NHERI) TallWood project, to demonstrate the resilience capabilities of the system. While the CLT rocking wall SFRS demonstrated excellent resilience capabilities, a dearth of data in mass timber (in terms of resilience considerations) were identified both as a part of the TTF methodology development and as a part of NHERI TallWood. To address some this lack of data, nail laminated timber (NLT) and dowel laminated timber (DLT) diaphragms were tested using quasi-static reversed cyclic loading, determining the lateral capacity of these systems as well as identifying damage states to better incorporate them into the TTF methodology. With the resilience of the CLT rocking wall system demonstrated, and several of the identified research data gaps addressed, the TTF methodology was applied to the two-story, six-story, and ten-story archetypes utilizing the CLT rocking wall system and varying the different structural components to create a database of TTF performance. A total of 243 SFRS designs were considered, and this database was leveraged using the developed resilience-based design guidance to estimate the TTF performance of two ten-story design examples. The research presented here demonstrates that it is possible to design tall mass timber buildings with resilience considerations, and that there are mass timber SFRS suitable for resilient design. While the findings focus on mass timber, the methodology itself is not limited to mass timber. The design guidance presented herein represents the first step towards a more prescriptive solution for TTF performance, with the potential for the incorporation of other structural systems and materials beyond the CLT rocking wall. In addition, there is a significant push to codify functionality, often termed "functional recovery", into U.S. design codes in the next 10 years. The TTF methodology directly considers functionality as a part of the method and this research and research like it will provide the foundation for the codification effort.
Keywords: functionality; resilience; seismic engineering; mass timber; CLT; rocking wall